Ultra-low pressure membrane-based bio-purification process for decentralized drinking water supply: Improved permeability and removal performance. (November 2018) - Tang, Xiaobin; Cheng, Xiaoxiang; Zhu, Xuewu; Xie, Binghan; Guo, Yuanqing; Wang, Jinlong; Ding, An; Li, Guibai; Liang, Heng
Abstract: Ultra-low pressure gravity-driven membrane (GDM) filtration has been proposed as a cost-efficiency alternative for the decentralized drinking water supply in terms of its simple operation and low energy consumptions, whereas its undesirable removals of dissolved organic compounds (DOC) and relatively low flux impede its widespread application. In order to improve its filtration performance, filter media (granular activated carbon (GAC), zeolite and bio-ceramsite) was directly coated on the membrane surface to engineer an integrated GDM system. The coating filter layer and bio-cake layer on the membrane surface could engineer a highly porous "multifunctional double layer" structure, which facilitated improvements of stabilized flux by 30%–120% relative to GDM control. Besides, coating filter media to GDM can efficiently combine the complementary performance between filter coat and GDM filtration, and thus the removals of CODMn were improved to 21%, 30% and 70% in bio-ceramsite, zeolite and GAC coated systems. Furthermore, the integrated GDM systems conferred much higher potentials in resisting the shock load of contaminants (e.g. organics, ammonia, iron and manganese) compared to GDM control. In addition, a low-aeration cleaning in presence of filter media scouring could efficiently improve the flux recovery from 35% to 50–94%, while the membrane integrity test indicated that such filter media scouring would not damage the membrane surface. Overall, these findings can hopefully spark improvements of both permeability and permeate quality in GDM filtration and bring relevant benefits to the applications of GDM technologies for decentralized drinking water supply. Highlights: Ultra-low pressure membrane-based bio-purification process was proposed. Coating filter layer to GDM engineers a highly porous "multifunctional double layer". Positive roles of bio-cake layer in removals of NH4 + -N, Fe and Mn were revealed. Engineering porous "multifunctional double layer" sparked flux improvements by 30%–120%. A low-aeration cleaning method based on the scouring by filter media was developed.